ATime-dependent sticking coefficient model for multi-species spacecraft material - Michael C. Fong (2018)
A general sticking coefficient theory based on the classical adsorption kinetics concept has been developed for predicting adsorption of either a single-species or a multi-species molecular substance on a surface in a rarefied gas environment. Development of the model involves integration of the first-order adsorption kinetics differential equation with time, where the attendant adsorption is of the Arrhenius type. From this integration, the single-species sticking coefficient is expressible as an exponential function of the ratio of the impingement time to the residence time. The corresponding multi-species sticking coefficient is defined as the sum of the products of the single-species sticking coefficient and the mass fraction of the individual species. The single-species theory has been verified by excellent theory/data agreement based on pertinent DC 704 oil outgassing/deposition test data. The multi-species theory has also shown good agreement with the R-2560 adhesive outgassing/deposition data provided that certain correction factors are incorporated in the correlation process. Since this theory does not require speculation or empiricism and yet has been verified by data, it represents an important analytical tool for predicting molecular contamination for spacecraft systems (especially for satellite interior), semi-conductor manufacturing, as well as other high-technology industry applications. © 2005 by the American Institute of Aeronautics and Astronautics, Inc. All rights reserved.